Moby Dick - Melville, Herman; Bogart, Shirley; Studio, Pablo Marcos (New York : Baronet Books, 1990)
This Graphic Novel Series features classic tales retold with attractive color illustrations. Educatiors using the Dale-Chall vocabulary system adapted each title. Each 70 page, softcover book retains key phrases and quotations from the original classics. Introduce literature to reluctant readers and motivate struggling readers. Students build confidence through reading practice. Motivation makes all the difference. What's more motivation then the expectation of success?
Primary
800-899
Keywords: Ahab, Captain (Fictitious character) -- Juvenile fiction; Whaling ships -- Juvenile fiction; Ship captains -- Juvenile fiction; Mentally ill -- Juvenile fiction; Whales -- Juvenile fiction; Sea stories; Adventure stories